The enhancement in dielectric properties for PVDF based composites due to the incorporation of 2D TiO2 nanobelt containing small amount of MWCNTs. (October 2021) - Ji, Wenjing; Zhao, Guojie; Hu, Guilin; Fan, Li; Deng, Hua; Fu, Qiang
Abstract: Film capacitors can be used as energy storage for fast storage and release energy, but the low energy density limits their applications. In our previous study, we have demonstrated that a small amount of 2D titanium dioxide (TiO2 ) nanobelts in PVDF could significantly enhance the energy density of these composite films. In order to increase the dielectric constant and energy density of these composites, multi-walled carbon nanotubes (MWCNTs) are introduced into these 2D TiO2 nanobelts obtained during electrospinning, and parallelly oriented along these 2D nanobelts. The shell formed by insulating TiO2 can avoid the formation of conductive network and realize high polarization efficiency. It's shown that when the ratio of MWCNTs and TiO2 in the composite filler is 1:30, the breakdown voltage of the filler can achieve 478 kV/mm, the polarizability is 8.34 μC/cm 2, and the energy density is increased from 2.87 J/cm 3 to 17.97 J/cm 3 comparing with neat PVDF.